Creative (and cultural) industry entrepreneurship in the 21st century policy challenges for and by policymakers - Hill, Inge (Emerald Publishing, 2025)
Both volumes of Creative (and Cultural) Industry Entrepreneurship in the 21st Century map and elucidate the adaptations and challenges faced by the creative professionals and the entrepreneurial solutions they have co-developed
Keywords: Aufsatzsammlung